Analyst Recommendations and Nasdaq Market Making Activity - Bruce Mizrach (Rutgers University, Department of Economics, 2003)
I investigate the linkage between liquidity provision by Nasdaq market makers and analysts in the same firm. Using three measures of market activity, I find that Nasdaq firms are more likely to provide buy side liquidity in anticipation of upgrades in the period 1999-2000. ECN activity supports this pattern. Firm level evidence shows that 15 of 42 market makers studied engage in significant pre-recommendation activity. I estimate cumulative abnormal returns of more than 75% and profits of almost 600 million in a sample of 47 large capitalization stocks.
Keywords: G24; G14; 330; analyst; Nasdaq; market maker; Betriebliche Liquidität; Aktienmarkt; Neuer Markt; Vereinigte Staaten